Mastering Microservices Architecture and Cloud Computing : In-Depth Strategies for Domain-Specific Optimization - Pankaj Singhal, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article explores the intricate landscape of microservices architecture and cloud computing, specifically focusing on domain-specific optimization strategies. It delves into the foundational principles of microservices, examining their synergistic relationship with cloud technologies and their transformative impact on modern software development. The article addresses critical aspects such as service-to-service communication, API management, and data security in distributed environments. It also investigates the role of cloud-native services, including serverless computing and container orchestration, in enhancing microservices performance. Analyzing real-world case studies and emerging trends, the article highlights how organizations can leverage these technologies to drive innovation and maintain a competitive edge. Key challenges in implementing and managing microservices architectures and strategies for overcoming them are discussed. The research emphasizes the importance of tailoring microservices to specific business needs and provides insights into performance tuning for high-traffic systems. This article offers a forward-looking perspective on the evolution of microservices and cloud computing by exploring future trends and considerations, including the potential impact of emerging technologies like edge computing and artificial intelligence. It serves as a valuable resource for IT professionals, architects, and decision-makers seeking to master these technologies and implement domain-specific optimizations effectively in their organizations.
Keywords: Microservices Architecture; Cloud-Native Optimization; Domain-Specific Strategies Distributed Systems Management; Service-Oriented Scalability